PENGARUH SKALA USAHA, UMUR USAHA, PENDIDIKAN DAN PELATIHAN AKUNTANSI TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KECAMATAN TEGALREJO KOTA YOGYAKARTA - Mintarsih, Ratna Ambar; Musdhalifah, Siti; Sudaryanto, Y (PRIMA EKONOMIKA, 2020)
The purpose of this study was to determine the effect of business scale, business age, education, accounting training on the use of accounting information in micro, small and medium enterprises in Tegalrejo District, Yogyakarta City. The data technique uses a questionnaire. Sampling for this study was based on determining the number of samples of 50 UMKM owners in Tegalrejo District, Yogyakarta City. Methods of data analysis in this study using descriptive analysis, multiple linear regression analysis, t test, F test and test of the coefficient of determination using SPSS 23. The results showed that partially, business scale and business age had a positive and significant effect on the use of accounting information on MSMEs. Accounting education and training variables have no effect on the use of information on MSMEs. Simultaneously, it shows that the business scale, business age, education, and accounting training together have an effect on the use of accounting information. Therefore, there is a demand for parties who have an interest in improving micro-businesses in Tegalrejo District, especially the Department of Industry, Trade and Cooperatives in Yogyakarta City to provide education and training on the use of accounting information in business operations. Keywords: MSMEs, business scale, business age, education, accounting training, use of accounting information.